2012
DOI: 10.1097/aln.0b013e318242a2ec
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane Remifentanil Interaction

Abstract: Background: Various pharmacodynamic response surface models have been developed to quantitatively describe the relationship between two or more drug concentrations with their combined clinical effect. We examined the interaction of remifentanil and sevoflurane on the probability of tolerance to shake and shout, tetanic stimulation, laryngeal mask airway insertion, and laryngoscopy in patients to compare the performance of five different response surface models. Methods: Forty patients preoperatively received d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…1, 2, 4 and 8 ng⋅ml −1 for groups A, B, C and D, respectively. The corresponding Ce PROP resulting in P TOL = 90% was obtained from the sigmoidal response function for a dichotomous effect [ 2 , 9 , 10 ]. where γ is the slope parameter, representing the steepness of the concentration-effect relationship, and U is the combined potency of the drugs according to where Ce50 PROP is the effect-site concentration of propofol resulting in P TOL = 0.5 if given alone, and Ce50 REMI is the Ce REMI that results in an increase of U by a factor 2 or an apparent decrease of Ce50 PROP by 50%.…”
Section: Methodsmentioning
confidence: 99%
“…1, 2, 4 and 8 ng⋅ml −1 for groups A, B, C and D, respectively. The corresponding Ce PROP resulting in P TOL = 90% was obtained from the sigmoidal response function for a dichotomous effect [ 2 , 9 , 10 ]. where γ is the slope parameter, representing the steepness of the concentration-effect relationship, and U is the combined potency of the drugs according to where Ce50 PROP is the effect-site concentration of propofol resulting in P TOL = 0.5 if given alone, and Ce50 REMI is the Ce REMI that results in an increase of U by a factor 2 or an apparent decrease of Ce50 PROP by 50%.…”
Section: Methodsmentioning
confidence: 99%
“…Sufentanil and remifentanil are opioid receptor agonists with a great analgesic effect during surgery ( 6 11 ). However, there are few comparative studies available on the application of the two agonists in the laparoscopic radical resection of colorectal cancer with TCI.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the Minto interaction term β, Diz et al [ 14 ] reported it as a positive number of 0.424; however, they only concluded that additivity exists because the β value did not differ significantly from the value of 0 due to its wide confidence interval. Heyse et al [ 16 ] reported the interaction term β between sevoflurane and remifentanil as 1.47, which turned to be significant.…”
Section: Discussionmentioning
confidence: 99%